Revitalisasi Pendidikan: Menyoal Format Nasionalisme Kita Jelang Indonesia Emas 2045 - Paturahman, Maman; Sudrajat, Yayan; Rejeki, Suyekti Kinanthi; Sari, Ni Wayan Ayu Permata (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2024)
There is no independence of a nation without nationalism. The birth of a country and national passion are always built by a strong sense of nationalism. Nationalism will never be obsolete and will remain the identity of every child of the nation and become the pride of the nation whatever "ism" they adhere to. Nationalism that fades will fade identity and weaken national pride. Therefore, it is necessary to have an effective educational format to maintain the spirit and passion of intergenerational nationalism so that we are not careless ideologically and culturally, especially in realizing a "Golden Indonesia" in 2045. Keywords: Educational Revitalization, Nationalism Format.